Comportamiento intra clase de los estudiantes de noveno año de educación básica del Colegio Técnico Ponce Enríquez cantón Ponce Enríquez, provincia del Azuay, 2012. - Bermeo Uyaguari, Jonathan Rolando (2015)
Society and culture are part of the knowledge of the world by individuality, thus the process of intra becomes in the process of learning in education. This paper determines the socio factors incidents in the intra student behavior ninth year of basic general education Technical College Ponce Enriquez, Azuay Province, Canton Ponce Enriquez, a situation that is affecting the normal development of teaching and learning activities, so it is proposed as the research problem.